Students’ Perception On Using Busuu App As Learning Vocabulary Media - Yufita Afifka; Ernita Daulay (South Sulawesi Education Development (SSED), 2024)
Busuu is a language learning application that displays interactive audio-visual features that can help students learn and acquire vocabulary well, especially English. However, many researchers who discuss the Busuu application generally discuss improving listening, but only a few researchers discuss students' perceptions in using the Busuu application as a medium for learning vocabulary. The purpose of this study was to explore students' perceptions of the Busuu application that has been used as a medium for learning vocabulary. This study uses a qualitative descriptive method, with questionnaires and interviews as data collection. The data collected were analyzed using thematic analysis. The results obtained from the questionnaire and interviews revealed that the Busuu application as a learning medium provides effectiveness for students as vocabulary learning 83.57% which is included in the good category and also Busuu is able to improve vocabulary, motivate students to be more active in learning . Furthermore, the results of this research also reveal other benefits of Busuu features such as interactive audio visuals and systematically arranged material, also there are some restrictions such as poor internet connections which can be an obstacle for users.